Occult olfactory neuroblastoma presenting with multiple bone metastases: a case report. Issue 48 (25th November 2020) - Zhou, Qi; Li, Zijian; Liu, Bei; Zhao, Long; Tian, Baohong; Wang, Lina; Xi, Yaming
Abstract: Rationable: Olfactory neuroblastoma (ONB) is a rare malignant tumor of the nasal cavity, the primary local symptoms are usually inconspicuous. Patients are often admitted to various specialties based on different primary symptoms, which may result in delayed diagnosis and even a misdiagnosis. Patient concerns: Here we report a case of ONB that presented initially as multiple ostealgia without any local symptoms of the tumor and primarily misdiagnosed as multiple myeloma. The patient was a 47-year-old female with bone pain at multiple sites. The initial diagnosis was considered as multiple myeloma. However, the morphologic examination of bone marrow suggested that the tumor cells originated from the nervous tissues. After the positron emission computed tomography scan, the primary lesion in the nasal cavity was located, and a biopsy was performed. Diagnosis: The final diagnosis of ONB was confirmed by histopathological tests. Interventions: The patient was treated with metronomic chemotherapy. Outcomes: The symptoms of bone pain were significantly relieved 3 months later. The emission computed tomography scan of the whole body bones and the magnetic resonance imaging of the head showed that the tumor size did not change significantly and proved a progression-free of the disease. Lessons: It is a reasonable strategy to identify the original latent tumor by a prompt positron emission computed tomography scan when the primary diagnosis indicates a metastatic disease, especially for the occult malignancies like ONB.